A dual mechanism fully blocks ethanol relapse: Role of vagal innervation. (20th January 2022) - Quintanilla, María Elena; Ezquer, Fernando; Morales, Paola; Santapau, Daniela; Ezquer, Marcelo; Herrera‐Marschitz, Mario; Israel, Yedy
Abstract: Previous studies showed that vagotomy markedly inhibits alcohol self‐administration. Present studies hypothesised that vagotomy significantly adds to the inhibition of alcohol relapse induced by drugs that reduce the alcohol‐induced hyperglutamatergic state (e.g., N‐acetylcysteine + acetylsalicylic acid). The alcohol relapse paradigm tested gauges the elevated alcohol intake observed in animals that had consumed ethanol chronically, were subjected to a prolonged alcohol deprivation and are subsequently allowed ethanol re‐access. Ethanol‐drinker rats (UChB) were exposed to 10% and 20% ethanol and water concurrently for 4 months, were alcohol deprived for 14 days and were thereafter allowed re‐access to the ethanol solutions. An initial binge‐like drinking episode is observed upon ethanol re‐access, followed by a protracted elevated ethanol intake that exceeds the predeprivation intake baseline. Prior to ethanol re‐access, animals were (i) administered N‐acetylcysteine (40 mg/kg/day) + acetylsalicylic acid (15 mg/kg/day), (ii) were bilaterally vagotomised, (iii) were exposed to both treatments or (iv) received no treatments. The initial binge‐like relapse intake and a protracted elevated ethanol intake observed after repeated ethanol deprivations/re‐access cycles were inhibited by 50%–70% by the administration of N‐acetylcysteine + acetylsalicylic acid and by 40%–70% by vagotomy, while the combined vagotomy plus N‐acetylcysteine + acetylsalicylic acid treatment inhibited both the initial binge‐like intake and the protracted ethanol intake by >95% ( p  < 0.001), disclosing a dual mechanism of ethanol relapse and subsequent inhibition beyond that induced by either treatment alone. Future exploration into the mechanism by which vagal activity contributes to ethanol relapse may have translational promise. Abstract : Alcohol relapse following chronic alcohol intake is markedly inhibited by the administration of (N‐acetylcysteine + acetylsalicylic acid; NAC + ASA) or by vagus nerve sectioning (vagotomy). The combination of both treatments fully blocks relapse ethanol intake.